PEBSI: a Monte Carlo simulator for bremsstrahlung arising from electrons colliding with thin solid-state targets - Weber, Günter; Märtin, Renate; Surzhykov, Andrey; Yerokhin, Vladimir; Stöhlker, Thomas (Nuclear instruments & methods in physics research. Section B, Beam interactions with materials and atoms, 2012)
We present a Monte Carlo code dedicated to the simulation of bremsstrahlung arising in collisions of polarized electrons with thin target foils. The program consists of an electron transport algorithm taking into account elastic electron-nucleus scattering and inelastic collisions with target electrons as well as a treatment of polarized-electron bremsstrahlung emission. Good agreement is found between the predictions of the electron transport code and data stemming from other simulation programs and experiments. In addition, we present first results from the bremsstrahlung simulation which indicate a significant decrease in the degree of linear polarization of bremsstrahlung even for the thinnest gold targets considered.